Gene expression patterns underlying parasite‐induced alterations in host behaviour and life history. Issue 2 (19th January 2016) - Feldmeyer, Barbara; Mazur, Johanna; Beros, Sara; Lerp, Hannes; Binder, Harald; Foitzik, Susanne
Abstract: Many parasites manipulate their hosts' phenotype. In particular, parasites with complex life cycles take control of their intermediate hosts' behaviour and life history to increase transmission to their definitive host. The proximate mechanisms underlying these parasite‐induced alterations are poorly understood. The cestode Anomotaenia brevis affects the behaviour, life history and morphology of parasitized Temnothorax nylanderi ants and indirectly of their unparasitized nestmates. To gain insights on how parasites alter host phenotypes, we contrast brain gene expression patterns of T. nylanderi workers parasitized with the cestode, their unparasitized nestmates and unparasitized workers from unparasitized colonies. Over 400 differentially expressed genes between the three groups were identified, with most uniquely expressed genes detected in parasitized workers. Among these are genes that can be linked to the increased lifespan of parasitized workers. Furthermore, many muscle (functionality) genes are downregulated in these workers, potentially causing the observed muscular deformations and their inactive behaviour. Alterations in lifespan and activity could be adaptive for the parasite by increasing the likelihood that infected workers residing in acorns are eaten by their definitive host, a woodpecker. Our transcriptome analysis reveals numerous gene expression changes in parasitized workers and their uninfected nestmates and indicates possible routes of parasite manipulation. Although causality still needs to be established, parasite‐induced alterations in lifespan and host behaviour appear to be partly explained by morphological muscle atrophy instead of central nervous system interference, which is often the core of behavioural regulation. Results of this study will shed light upon the molecular basis of antagonistic species interactions.